2015
DOI: 10.2147/rmhp.s89473
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial support and parents' social life determine the self-esteem of orphan children

Abstract: Parental death affects the life of children in many ways, one of which is self-esteem problems. Providing psychosocial support and equipping orphans play a vital role in their lifes. A cross-sectional study was conducted on 7–18-year-old orphans at 17 local districts of Gamo Gofa Zone, Southern Regional State of Ethiopia. From a total of 48,270 orphans in these areas, 4,368 were selected using stratified simple random sampling technique. Data were collected with a designed questionnaire based on the Rosenberg’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 5 publications
1
11
0
Order By: Relevance
“…This problem is in line with research in Africa, which showed that orphan adolescents have a higher incidence of grieving problems, post-traumatic stress, depression, suicidal thoughts, anxiety, behavior problems, and negative outlook, than non-orphan adolescents [28], [29], [30], [31]. More specifically, this study is also in line with Erango and Ayka [32] which stated that 59% of children experience self-esteem problems followed by emotional problems including anxiety as much as 14.73% [7] and at least 12.7% experience depression [7].…”
Section: Discussionsupporting
confidence: 92%
“…This problem is in line with research in Africa, which showed that orphan adolescents have a higher incidence of grieving problems, post-traumatic stress, depression, suicidal thoughts, anxiety, behavior problems, and negative outlook, than non-orphan adolescents [28], [29], [30], [31]. More specifically, this study is also in line with Erango and Ayka [32] which stated that 59% of children experience self-esteem problems followed by emotional problems including anxiety as much as 14.73% [7] and at least 12.7% experience depression [7].…”
Section: Discussionsupporting
confidence: 92%
“…Orphan hood caused by parental death, disrupted bonds during childhood affect the life of children in a negative way including the risk of being low in self-esteem (Erango and Ayka, 2015). There is a diversity and complexity of reasons that determine the mothers' role in the education of their children (Anyikwa and Obidike, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Orphanhood leads to various problems often to prejudice, reduced access to health and school services, challenges to the basic physiologic needs and other factors that can impact their future [ 1 ]. The death of one or both parents has a profound and lifelong impact on the psychological wellbeing of children that affects every aspect of their lives; to learn, to be healthy, to play, to be productive, and to relate well to other people as they develop [ 2 ].…”
Section: Introductionmentioning
confidence: 99%